Foot and mouth disease vaccine efficacy in Africa: a systematic review and meta-analysis - Wubshet, Ashenafi Kiros; Werid, Gebremeskel Mamu; Teklue, Teshale; Zhou, Luoyi; Bayasgalan, Chimedtseren; Tserendorj, Ariunaa; Liu, Jinjin; Heath, Livio; Sun, Yuefeng; Ding, Yaozhong; Wang, Wenxiu; Zaberezhny, Alexei D.; et al. (Frontiers in Veterinary Science, 2024)
Background: Several factors, such as diverse serotypes, vaccination methods, weak biosecurity, and animal movements, contribute to recurrent Foot-and-Mouth Disease Virus (FMDV) outbreaks in Africa, establishing endemicity. These outbreaks cost over $2 billion annually, prompting a highpriority focus on FMDV vaccination. Despite extensive efforts, vaccine efficacy varies. This study aims to evaluate routine FMD vaccines in Africa via systematic review and meta-analysis. methods: A systematic review and meta-analysis were carried out following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Meta-analysis was conducted to assess the efficacy of FMDV vaccination using the metafor package of R. Results: Vaccinated animals have roughly a 69.3% lower chance of FMDV infection compared to unvaccinated animals, as indicated by the pooled results from the random-effects model, which showed a risk ratio (R.R.) of 0.3073. There was a statistically significant heterogeneity (p < 0.05) across all of the included articles. Conclusions: Overall findings suggest that if properly planned and implemented, FMDV vaccination programmes and strategies in Africa could help control the spread of the disease throughout the continent and beyond.